The Role of Platelet-Rich Plasma in Promoting Cartilage Integration and Chondrocyte Migration. Issue 7 (21st July 2017) - Sermer, Corey; Kandel, Rita; Anderson, Jesse; Hurtig, Mark; Theodoropoulos, John S.
Objectives: Current therapies for cartilage repair either do not result in regeneration of articular cartilage, or there is inadequate integration with the host tissue leading to failure of the repair. Thus, there is an interest in developing alternative approaches. The mechanisms of cartilage integration remain relatively unknown, however it is believed that chondrocyte migration is crucial to this process. Previously, we showed that platelet rich plasma (PRP) enhances in vitro cartilage tissue formation. We hypothesized that PRP will enhance the integration of bioengineered cartilage with native cartilage due to increased matrix accumulation at the interface and that PRP could promote chondrocyte migration. Methods: Isolated bovine chondrocytes were seeded on a porous bone substitute and grown in vitro to form osteochondral-like tissue. After 7 days the biphasic constructs were soaked in PRP for 30 minutes prior to implantation into the core of a ring-shaped osteochondral explant. Controls were not soaked in PRP. The resulting implant-explant construct was cultured in a stirring bioreactor for 2 weeks (contact model). Alternatively, the PRP soaked biphasic construct was placed 2mm away from a native cartilage/bone plug of equal dimensions to assess chondrocyte migration between the two tissues (non-contact model). The integration zone was visualized histologically. A push-out test was performed to assess the strength of integration. Matrix accumulation at the zone of integration was assessed biochemically and the gene expression of the cells in this region was assessed by RT-PCR. Cell migration was evaluated by video microscopy over 8 days. Significance (p<0.05) was determined by a χ 2 test, a student's t-test or one-way ANOVA with tukey's post hoc. Results: PRP soaked implants (contact model) integrated with host tissue in 73% of samples, whereas control implants integrated in 19% of samples (p<0.05). The integration strength was significantly increased in the PRP soaked implant group compared to controls (219 ± 35.4 kPa and 72.0 ± 28.5 kPa, respectively, p<0.05). This correlated with an increase in glycosaminoglycan and collagen accumulation in the region of integration in the PRP treated implant group (p<0.05). Immunohistochemical studies revealed that the integration zone was rich in collagen type II and aggrecan. The cells at the zone of integration in the PRP soaked group had a 3.5 fold increase in matrix metalloproteinase 13 (MMP13) gene expression (p<0.05) compared to controls. In the non-contact cultures, a network of fibers developed to connect the PRP soaked construct to the native plug. No fibers formed when the constructs were not soaked in PRP. Time-lapse videos showed chondrocytes with a round phenotype migrating along the fibers and undergoing cell division within 24 hours. These cells came from the bioengineered cartilage whereas migrating cells from native cartilage were only seen after 5 days in select cultures. After 2 weeks, the cells deposited cartilage-like matrix around the fibers as seen histologically. A single layer of cells expressed MMP13 on the outer aspects of the tissue. Conclusion: PRP soaked bioengineered cartilage implants showed improved integration with native cartilage compared to non-soaked implants perhaps due to increased matrix accumulation. Chondrocytes grew out from the in vitro formed tissue and migrated along fibers after PRP soaking. The contribution of these cells to integration requires further study.